Effects of the herbicides benfluralin, metribuzin and propyzamide on the survival and weight of earthworms (Octodrilus complanatus) - Ilias S. TRAVLOS; Trisevgeni GKOTSI; Ioannis ROUSSIS; Charis-Konstantina KONTOPOULOU; Ioanna KAKABOUKI; Dimitrios J. BILALIS (Plant, Soil and Environment, 2017)
Extended pesticide use might be of high risk for several non-target organisms like earthworms. Herbicides represent a major part of the total pesticides used; however, their effects on soil organisms have been only partially studied. The effects of the herbicides benfluralin, metribuzin and propyzamide at different rates on the survival and weight of earthworms (Octodrilus complanatus) were determined and compared in this study. Our results revealed significant effects of benfluralin, metribuzin and propyzamide on growth and survival of earthworms. Moreover, there was a significant effect of herbicide rate and time after treatment. For several herbicides, the highest weight reduction was obtained for double the recommended rate and was up to 70% compared to the untreated soil. This study highlights the importance of not exceeding the recommended rates of herbicides, while further studies in a range of conditions are certainly required.